Cumulative Birth Rates with Linked Assisted Reproductive Technology Cycles - Luke, Barbara (2012)
BACKGROUND: Live-birth rates after treatment with assisted reproductive technology have traditionally been reported on a per-cycle basis. For women receiving continued treatment, cumulative success rates are a more important measure. METHODS: We linked data from cycles of assisted reproductive technology in the Society for Assisted Reproductive Technology Clinic Outcome Reporting System database for the period from 2004 through 2009 to individual women in order to estimate cumulative live-birth rates. Conservative estimates assumed that women who did not return for treatment would not have a live birth; optimal estimates assumed that these women would have live-birth rates similar to those for women continuing treatment. RESULTS: The data were from 246,740 women, with 471,208 cycles and 140,859 live births. Live-birth rates declined with increasing maternal age and increasing cycle number with autologous, but not donor, oocytes. By the third cycle, the conservative and optimal estimates of live-birth rates with autologous oocytes had declined from 63.3% and 74.6%, respectively, for women younger than 31 years of age to 18.6% and 27.8% for those 41 or 42 years of age and to 6.6% and 11.3% for those 43 years of age or older. When donor oocytes were used, the rates were higher than 60% and 80%, respectively, for all ages. Rates were higher with blastocyst embryos (day of transfer, 5 or 6) than with cleavage embryos (day of transfer, 2 or 3). At the third cycle, the conservative and optimal estimates of cumulative live-birth rates were, respectively, 42.7% and 65.3% for transfer of cleavage embryos and 52.4% and 80.7% for transfer of blastocyst embryos when fresh autologous oocytes were used. CONCLUSIONS: Our results indicate that live-birth rates approaching natural fecundity can be achieved by means of assisted reproductive technology when there are favorable patient and embryo characteristics. Live-birth rates among older women are lower than those among younger women when autologous oocytes are used but are similar to the rates among young women when donor oocytes are used. (Funded by the National Institutes of Health and the Society for Assisted Reproductive Technology.)